What's with the mutant in the microscope? - Johnson, Kevin (Kevin Walter); White, James R. (James Robert), 1962- (Minneapolis, Minn. : Bethany House Publishers, 1952)
Explains the arguments in the creation versus evolution debate, answers the claims that humans are the product of chance, and presents a clear case for the Biblical teachings on creationism.
Your uncle was fuzzy, or was he? -- The rat in the snake -- He who has the most kids wins -- The genes in your jeans -- The so-called simple cell -- Captain Protein and the space zombies -- Amateur autopsy -- The God who gives you toast.
Includes bibliographical references (p. [141]-142).
Keywords: Creationism -- Juvenile literature; Evolution (Biology) -- Religious aspects -- Christianity -- Juvenile literature; Creationism; Evolution